The Influence of Strategy Implementation on the Performance of Micro Enterprises in Ruiru Sub County, Kiambu County, Kenya (International Journal of Management and Sustainability, 2017)
Two questions guide this research on the influence of strategy implementation to the performance of the micro enterprises in the Ruiru Sub County, Kiambu County, Kenya. The first is whether micro enterprises in Ruiru Sub County carry out strategic planning including strategy implementation. The second is whether strategy implementation has any competitive influence on their performance. Most literature and research on strategic planning is on big firms (Pearce and Robinson, 2007). In Kenya strategic planning is relatively new and less common in small enterprises. Micro enterprises ranking at the bottom of the pyramid of businesses in Kenya are more likely to ignore it. Although they contribute heavily to service delivery and job creation many of them are handicapped in growth and expansion. Data was collected on a sample drawn from 737 micro enterprises from 3 different industries in Ruiru Sub County using descriptive research design. Stratified random sampling was used with a 20% sample size which was 147 elements. Data was collected from the micro enterprises’ owner-managers by use of self-administered or interview administered questionnaires. Data was analyzed using descriptive and inferential statistics with computer software. The findings conclude that micro entrepreneurs in Ruiru Sub County make business strategies and implement them and strategy implementation significantly influences the performance of these micro enterprises. For the micro entrepreneurs who engaged in strategy implementation the average rate of success on the three performance variables of profits, business turnover and market positioning was 75% while those who did not implement strategy was 25%.